Analisis Cluster Pada Pengelompokan Siswa Diktuk Bintara Polri TA. 2018/2019, SPN Singaraja - Polda Bali Menggunakan K-Means dan K-Harmonic Means - i gede aris gunadi (STMIK Sinar Nusantara, 2019)
Education is basically one step to improve and develop all aspects of human beings. Education is not only in the form of science, but also in the form of values, skills and attitudes, so that in education it is expected to be able to make a person intelligent, skilled and be able to behave according to the prevailing norms. Mathematics is one of the subjects taught since elementary school education. Geometry and measurement are aspects of basic competencies found in elementary school mathematics learning ranging from class I to class VI. To make a child have good geometry measurement skills, the teacher (parent, teacher or family) must have a means or media that can train children's geometry measurement skills in an interesting and fun way. The purpose of this study was to create a media to train geometry measurement capabilities, especially for class V through an Android-based application, the application created was packaged in the form of an educational game. The game was developed using SDLC with V-models and the game was tested through blackbox, installation tests and questionnaires.